Low prevalence of neural autoantibodies in perioperative cerebrospinal fluid samples of epilepsy surgery patients: A multicenter prospective study - Mojžišová, Hana; Elišák, Martin; Krýsl, David; Hanzalová, Jitka; Kalina, Adam; Petržalka, Marko; Doležalová, Irena; Červenka, Matěj; Cvičková, Barbora; Leško, Robert; Šroubek, Jan; Sochůrková, Daniela; et al. (Epilepsia, 2024)
OBJECTIVE: Refractory epilepsy may have an underlying autoimmune etiology. Our aim was to assess the prevalence of neural autoantibodies in a multicenter national prospective cohort of patients with drug-resistant epilepsy undergoing epilepsy surgery utilizing comprehensive clinical, serologic, and histopathological analyses. METHODS: We prospectively recruited patients undergoing epilepsy surgery for refractory focal epilepsy not caused by a brain tumor from epilepsy surgery centers in the Czech Republic. Perioperatively, we collected cerebrospinal fluid (CSF) and/or serum samples and performed comprehensive commercial and in-house assays for neural autoantibodies. Clinical data were obtained from the patients' medical records, and histopathological analysis of resected brain tissue was performed. RESULTS: Seventy-six patients were included, mostly magnetic resonance imaging (MRI)-lesional cases (74%). Mean time from diagnosis to surgery was 21 ± 13 years. Only one patient (1.3%) had antibodies in the CSF and serum (antibodies against glutamic acid decarboxylase 65) in relevant titers; histology revealed focal cortical dysplasia (FCD) III (FCD associated with hippocampal sclerosis [HS]). Five patients' samples displayed CSF-restricted oligoclonal bands (OCBs; 6.6%): three cases with FCD (one with FCD II and two with FCD I), one with HS, and one with negative histology. Importantly, eight patients (one of them with CSF-restricted OCBs) had findings on antibody testing in individual serum and/or CSF tests that could not be confirmed by complementary tests and were thus classified as nonspecific, yet could have been considered specific without confirmatory testing. Of these, two had FCD, two gliosis, and four HS. No inflammatory changes or lymphocyte cuffing was observed histopathologically in any of the 76 patients. SIGNIFICANCE: Neural autoantibodies are a rare finding in perioperatively collected serum and CSF of our cohort of mostly MRI-lesional epilepsy surgery patients. Confirmatory testing is essential to avoid overinterpretation of autoantibody-positive findings.
Keywords: Autoantibodies; Epilepsy; Magnetic Resonance Imaging; magnetická rezonanční tomografie; epilepsie; Humans; malformace mozkové kůry; prevalence; Drug Resistant Epilepsy; neural antibodies; CSF; lidé; epilepsy surgery; Malformations of Cortical Development; refrakterní epilepsie; epilepsy; autoprotilátky; Retrospective Studies; GAD65; Prevalence; retrospektivní studie; prospektivní studie; Prospective Studies